Pathosformel : Aby Warburg ja avain tunteiden taidehistoriaan - Vuojala, Petri (1997)
The subject of the study is outlined in the concept of "Pathosformel", which is probably the best known term created by Aby Warburg. The study focuses on the meanings, the context, the historical applications and the theoretical background of the concept, which can be defined at the most general level as a classical formula of pathetic expressions. The study is composed of three parts: in the first section (Warburg: Towards the Art History of Lost Realities), a general description of the Warburg method is given. In the next chapter (Pathosformel as a Concept of the Art History of Emotions), the approach is theoretical: the use, meanings, and context of the concept are studied from an analytical point of view. In it the method and theory of Warburg is understood not as a doctrine (Lehrgebäude) but rather as a collection of problems which were described by him in the form of loosely connected aphorisms. In the third part (Pathosformel and its Functions in the History of Styles of the Renaissance), the concept and its applications are approached historically. The chapter opens a view into the Warburgian kaleidoscope of Renaissance art, in which the artistic development is seen as constantly changing constellations of styles. The conceptual environment of the Pathosformel is also considered in the study. Terms and concepts like empathy (Einfühlung), coinage (Prägung), social memory (soziales Gedächtnis), clashing and harmony (Auseinendersetzung und Ausgleich), polarity (Polarität), which have a specific value in Warburg's theory of art, and theory of history and creativity, are brought into the discussion. Also, the philosophical dimensions of the famous Warburg slogans "You live, but do not harm me" (Du lebst aber tust mir nichts), and "The Good God dwells in detail" (Der liebe Gott steckt in Detail) are studied. The main objective of the study has been in the intellectual reconstruction of Warburg's problematics, in reformulating and clarifying his questions and views. The dissertation follows the advice of Gertrud Bing, a colleague of Warburg, to follow Warburg's thought "in its consistency and fearlessness". The primary source material, on which the research is based, consists, along with Warburg's published texts, of his unpublished manuscripts (Nachlass). Of those Warburg files two ought to be mentioned especially: "Elementary Fragments for Pragmatic Theory of Expression" (Grundlegenden Bruchstücke zu einer pragmatischen Ausdruckskund) and "Introduction to the Early Renaissance – the Hamburg Lectures" (Einführung in die Kultur der Italienischen Frührenaissance). The analysis of the theoretical background of the concept "Pathosformel" (i.e. the social and psychological theory of the body movements and body language) is based on the above mentioned and the description of the stylistic development of Renaissance art on the latter file.